2008
DOI: 10.1590/s0100-204x2008001000010
|View full text |Cite
|
Sign up to set email alerts
|

Cell suspension culture and plant regeneration of a Brazilian plantain, cultivar Terra

Abstract: -The objective of this study was to establish cell suspension culture and plant regeneration via somatic embryogenesis of a Brazilian plantain, cultivar Terra Maranhão, AAB. Immature male fl owers were used as explant source for generating highly embryogenic cultures 45 days after inoculation, which were used for establishment of cell suspension culture and multiplication of secondary somatic embryos. Five semisolid culture media were tested for differentiation, maturation, somatic embryos germination and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The addition of glutamine to the M3 media may contribute to some amount of nitrogen source in the medium, which may have helped in improving the rate of somatic embryo maturation. The presence of glutamine facilitated completion of maturation of somatic embryos as reported by Morais-Lino et al [25]. The results indicated that exogenous supplementation of amino acid can serve as a nitrogen source for the synthesis of the protein which is important for embryo differentiation and maturation.…”
Section: Resultssupporting
confidence: 65%
“…The addition of glutamine to the M3 media may contribute to some amount of nitrogen source in the medium, which may have helped in improving the rate of somatic embryo maturation. The presence of glutamine facilitated completion of maturation of somatic embryos as reported by Morais-Lino et al [25]. The results indicated that exogenous supplementation of amino acid can serve as a nitrogen source for the synthesis of the protein which is important for embryo differentiation and maturation.…”
Section: Resultssupporting
confidence: 65%
“…Callus with four months, obtained on the first experiment, were transferred to Erlenmeyer flasks (125 mL) containing 15 mL of different culture mediums: MRT medium, (½ MS medium, 8.8 µM BA, 1.34 µM de NAA, 554.3 µM inositol, 400 mg L-1 malt, 100 mg L-1 de casein and 1 mL of vitamins solution (1g thiamin, 0.1 g pyridoxine, 0.1 g nicotinic acid and 0.1 mg L-1 glycine), MGM medium (1/2 MS medium, 2.57 µM AIA and 1.11 µM BA), CNPMF medium (MS medium, 4.52 µM 2,4-D, 100 mg L-1 glutamine, 10 mg L-1 ascorbic acid, 44.5 g L-1 sucrose and pH 5.3) (Morais-Lino et al, 2008) or MA2 medium (MS salt medium, vitamins (1.0 mg.L-1 biotin, 2.0 mg L-1 glycine, 0.5 mg L-1 nicotinic acid, 0.5 mg L-1 pyridoxine.HCl, 0.1 mg L-1 thiamin.HCl), 100 mg L-1 inositol, 100 mg L-1 malt extract, 100 mg L-1 glutamine, 45 g L-1 sucrose, 4.52 µM 2,4-D and pH 5.3 (Strosse et al, 2003). The pH was adjusted to 5.8 before autoclaving at 121 °C for 20 min.…”
Section: Results E Discussionmentioning
confidence: 99%
“…The cell suspensions with high regeneration capacity were commonly used for mass clonal propagation and these cells were also the only source to regenerate plant materials for inducing mutations and genetic engineering (Strosse et al, 2006). In situ gene expression analysis resolved the contradictory relationship between expression of developmental marker genes and cell fate in different culture systems (Miguel and Marum, 2011) and provided a more exact description of when and how embryogenic cells are formed in culture (Soriano et al, 2014). In the present investigation, secondary somatic embryos were observed during SEM studies of embryogenic callus.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2005) established embryogenic cell suspensions and plant regeneration of the dessert banana 'Williams' (Musa AAA, group). Morias -Lino et al (2008) reported cell suspension culture and plant regeneration of a Brazilian plantain, cultivar 'Terra' from immature male flowers, and secondary somatic embryos were reported from the suspension culture. Molecular genetics studies have also shown that ectopic expression of a specific embryoand meristem-expressed transcription factors or loss of certain chromatin-modifying proteins induces spontaneous somatic embryogenesis (Horstman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%